2018
DOI: 10.2147/ott.s160428
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of long noncoding RNA 00152 (LINC00152) inhibits human retinoblastoma progression

Abstract: BackgroundA growing body of evidence supports the involvement of long noncoding RNA 00152 (LINC00152) in the progression and metastasis of multiple cancers. However, the exact roles of LINC00152 in the progression of human retinoblastoma (RB) remain unknown. We explored the expression and biological function of human RB.Materials and methodsThe expression level of LINC00152 in RB tissues and cells was analyzed using quantitative real-time PCR. The function of LINC00152 was determined using a series of in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Accumulating literatures have highlighted that the expression change of lncRNAs has critical and clinically predictive roles in tumorigenesis (Elchuri et al, 2018). More and more lncRNAs were repor- (Hu et al, 2018), MT1JP (Bi et al, 2018), LIN00152 (Li et al, 2018), CCAT1 (Zhang et al, 2017), BANCR (Su et al, 2015), H19 (Zhang et al, 2018a), BDNF-AS (Shang et al, 2018), MALAT1 (Liu et al, 2017) and HOTAIR (Dong et al, 2016). Except for MT1JP and BDNF-AS, which are down-regulated and act as a tumor suppressor gene in RB, other lncRNAs are all up-regulated in RB and promote RB progression.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating literatures have highlighted that the expression change of lncRNAs has critical and clinically predictive roles in tumorigenesis (Elchuri et al, 2018). More and more lncRNAs were repor- (Hu et al, 2018), MT1JP (Bi et al, 2018), LIN00152 (Li et al, 2018), CCAT1 (Zhang et al, 2017), BANCR (Su et al, 2015), H19 (Zhang et al, 2018a), BDNF-AS (Shang et al, 2018), MALAT1 (Liu et al, 2017) and HOTAIR (Dong et al, 2016). Except for MT1JP and BDNF-AS, which are down-regulated and act as a tumor suppressor gene in RB, other lncRNAs are all up-regulated in RB and promote RB progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu et al reported that XIST promoted RB progression partially by modulating the miR-124/STAT3 axis 19. Li et al demonstrated that knockdown of LINC00152 significantly inhibited RB cell growth in vitro and in vivo 20. Zhang et al found that H19 inhibited RB progression via counteracting the roles of miR-17–92 cluster 21.…”
Section: Discussionmentioning
confidence: 99%
“…PlncRNA-1 (prostate cancer-up-regulated long noncoding RNA 1) modulates carbonyl reductase 3 (CBR3) activity, and LINC00152 (long noncoding RNA00152) inactivates Ki-67, Bcl-2, and MMP-9 at the post-transcriptional level. In both cases increased proliferation, invasion and migration were observed (Li et al, 2018b;Wang et al, 2018c).…”
Section: Ocular Malignancymentioning
confidence: 88%